HAMBATAN MAHASISWA DALAM PELAKSANAAN PRAKTIK PENGALAMAN LAPANGAN BIMBINGAN DAN KONSELING (PPLBK) SEKOLAH (Studi terhadap Mahasiswa BK 2010 STKIP PGRI Sumatera Barat) - Puspa, Dewi - (Bimbingan dan Konseling, 2014)
Background of this research was the counseling studentsâ barrier during teaching practice in the school. Based on observation that researcher done in STKIP PGRI on January 15th 2014, there were counseling students whose personal barriers and social barriers in teaching practice. The counseling studentsâ barriers were easily tired and dizzy, criticizing each other, and not compact during teaching practice. Moreover, the purposes of this research were to know the personal barriers and social barriers of counseling students in teaching practice.This research was quantitative descriptive. The population of this research were all counseling students that doing teaching practice at first semester academic year 2013. The population were 197 persons. From the population, the researcher chose 66 persons as sample by using insidental sampling technique. The instrument of this research was questionnaire. In addition, to analyze the data, researcher used percentage technique.The result of this research revealed about counseling studentsâ barriers of 2010 STKIP PGRI West Sumatera in teaching practice. The results of this research were 1) Personal barriers are in category of many obstacles; 2) Social barriers are in category of many obstacles. Based on the result of this research, the researcher suggests the counseling students to have a good personal and social readiness in teaching practice. For counseling department, the result of this research is as input for improving the quality of counseling students as teacher candidate. Furthermore, this research improves the researcherâ insight about personal barriers and social barriers of counseling student in teaching practice